Immunomodulatory Drugs Exert Anti-Leukemia Effects in Acute Myeloid Leukemia by Direct and Immunostimulatory Activities - Le Roy, Aude; Prébet, Thomas; Castellano, Rémy; Goubard, Armelle; Riccardi, Florence; Fauriat, Cyril; Granjeaud, Samuel; Benyamine, Audrey; Castanier, Céline; Orlanducci, Florence; Ben Amara, Amira; Pont, Frédéric; et al. (Frontiers in Immunology, 2018)
Immunomodulatory drugs (IMiDs) are anticancer drugs with immunomodulatory, anti-angiogenesis, anti-proliferative and pro-apoptotic properties. IMiDs are currently used for the treatment of multiple myeloma, myelodysplastic syndrome and B-cell lymphoma, however little is known about efficacy in acute myeloid leukemia (AML). We proposed in this study to investigate the relevance of IMiDs therapy for AML treatment. We evaluated the effect of IMiDs on primary AML blasts (n=24), and the impact in NK cell-mediated immunosurveillance of AML. Using primary AML cells and an immunodeficient mouse leukemia xenograft model, we showed that IMiD induce AML cell death in vitro and impair leukemia progression in vivo. In addition, treatment of AML blasts with IMiDs resulted in enhanced allogeneic NK cell anti-leukemia reactivity. Treatment by IMiD of AML blasts enhanced lysis, degranulation and cytokine production by primary allogeneic NK cells. Furthermore, the treatment with lenalidomide of patients with myeloid malignancies resulted in NK cell phenotypic changes similar to those observed in vitro. IMiDs increased CD56 and decreased NKp30, NKp46 and KIR2D expression on NK cells. Finally, AML blasts treatment with IMiDs induced phenotypic alterations including downregulation of HLA-class I. The effect of IMiD was not correlated with Cereblon expression and A/G polymorphism in AML cells. Our data revealed, a yet unobserved, dual effects on AML affecting both AML survival and their sensitivity to NK immunotherapy using IMiDs. Our study encourages continuing investigation for the use of IMiDs in AML, especially in combination with conventional therapy or immunotherapy strategies.